Studi Eksplorasi Mengenai Filosofi, Kandungan Gizi, dan Nilai Makanan dalam Upacara Adat Suku Tengger: An Exploratory Study on the Philosophy, Nutritional Content, and Food Value in Traditional Ceremonies of the Tengger Tribe - Muniroh, Lailatul; Rifqi, Mahmud Aditya; Socadevia, Annisa (Universitas Airlangga, 2025)
Background: The Tengger Tribe strongly upholds traditional and cultural aspects in their daily lives, particularly in the preparation of food offerings that carry deep philosophical meanings. In addition to their cultural significance, these foods also possess nutritional content and value from the perspective of the Tengger Tribe. Objectives: This study aimed to explore the philosophy, nutritional content, and food value of offerings served in the traditional ceremonies of the Tengger Tribe. Methods: This exploratory qualitative study was conducted in Wonokitri Village, Tosari District, Pasuruan Regency, East Java, Indonesia. The research informants included the village head, traditional leaders, religious leaders, and community leaders of the Tengger Tribe. The research variables encompassed the philosophy of food, its nutritional content, and its cultural significance in the traditional ceremonies of the Tengger Tribe. Results: The study found that traditional ceremonies are routinely performed, including Yadna Kasada, Karo, Unan-Unan, Pujan Mubeng, and Barikan. Additionally, individual ceremonies such as Entas-Entas, Tugel Kuncung, Among-Among, and weddings are also significant. Each ceremony features specific food offerings, primarily jadah, pasung, pepes, and red-and-white jenang, which are rich in carbohydrates and have a distinct sweet taste. The philosophy behind these offerings has been passed down through generations. Conclusions: The Tengger Tribe remains deeply committed to their traditional ceremonies. Food offerings in these ceremonies are an inherited tradition with profound philosophical meanings, and their cultural and nutritional value continues to be upheld, ensuring their sustainability. The primary foods used in these ceremonies are traditional cakes, which are high in carbohydrates.